Upaya Meningkatkan Hasil Belajar Matematika melalui Penerapan Metode Pemberian Tugas Siswa Kelas III SD Negeri 46 Cakranegara - Nurtini, Nurtini (Lembaga Yasin AlSys, 2023)
The objectives to be achieved in this research are: to find out the increase in Mathematics learning outcomes by implementing the method of giving assignments to Class III Students of SD Negeri 46 Cakranegara in the Academic Year 2022/2023. This research consists of three cycles. The data collection instruments in this study were teacher performance observation sheets, student activity, and evaluation questions at the end of each cycle. Based on the results of the research and discussion, it can be concluded that the learning outcomes of students III at SD Negeri 46 Cakranegara in the 2022/2023 school year, with the assignment method can be improved with the final results of the study being the class average value in the initial conditions of 69.95 or classical completeness of 65.85 %, to 74.07 or 75.61% classical completeness in cycle I, increased to an average of 78.44 or 82.93% in cycle II and increased to an average test of 86.20 or 95.12% in cycle III. From the results of student observations it was shown that there was an increase in student activity in cycle I obtained a score of 19 or 67.86% to 21 or 75.00% in cycle II and 25 or 89.29% in cycle III. The increase in student activity in learning Mathematics is supported by the increase in teacher activity in maintaining and improving the learning atmosphere using the assignment method, this can be seen from the observations of teacher activities where in cycle I a score of 25 or 69.44% was obtained, becoming 27 or 75, 00% in cycle II and increased to 32 or 88.89% in cycle III.